Innovative Approaches To Developing Volitional Qualities In Adolescents Based on Modern Psychotechnologies - Khamzayevich, Akhatov (Jurnal Psikologi, 2025)
This study explores innovative methods for developing volitional qualities in adolescents through the application of modern psychotechnologies. Given the emotional instability and identity challenges faced by adolescents, fostering willpower, self-regulation, and perseverance is essential for their successful social integration. The research investigates how digital tools, cognitive-behavioral training, reflective techniques, and self-monitoring applications contribute to the enhancement of volitional development. An experimental design was used to compare the progress of students who participated in a psychotechnology-based intervention program with those following traditional educational methods. The results showed statistically significant improvements in self-control, goal-directedness, emotional regulation, and social responsibility in the experimental group. These findings highlight the transformative potential of psychotechnologies in shaping adolescent behavior and strengthening their ability to make autonomous, purposeful decisions in complex environments.